At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
x = -1, 7
Step-by-step explanation:
Given question is incomplete; find the complete question in the attachment.
x² - 6x - 7 = 0
Step 1,
Isolate the constant by ADDING 7 both the sides of the equation.
x² - 6x - 7 + 7 = 0 + 7
x² - 6x = 7
Step 2
Add 9 to both sides of x² - 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
x² - 6x + 9 = 7 + 9
Step 3
Write the trinomial x² - 6x + 9 as (x - 3) squared.
x² - 2(3)x + 9 = 16
(x - 3)² = 4²
Step 4
Use the square root property of the equality to get x - 3 = ± 4
(x - 3)² = 4²
[tex]\sqrt{(x-3)^2}=\sqrt{4^2}[/tex]
(x - 3) = ±4
Step 5
Isolate the variable to get solution of -1 and 7
x - 3 = ± 4
x = -3 ± 4
x = -1, 7
Answer:
1. Isolate the constant by adding 7 to both sides of the equation.
2. Add 9 to both sides of x2 – 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
3. Write the trinomial x2 – 6x + 9 as x – 3 squared.
4. Use the square root property of equality to get x – 3 = ± 4.
5. Isolate the variable to get solutions of –1 and 7.
Step-by-step explanation:
just completed this on edge
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.